The narrative labyrinths of Italo Calvino and Umberto Eco: encyclopedia, "total novel" and the cosmic vocation of literature - Vinci, Maria Gloria (2015)
Ropewalking in dialectical tension between order and chaos, cosmos and fragment, opening and closing, code searching and deconstructive abandonment, both Italo Calvino and Umberto Eco recognize the creative and gnoseological potential of literature, its ability to open itself directly to the multi-faceted variations of the world, to record and give an interpretation to the kaleidoscopic character of man's experience and languages. If literature aims at mapping the intricate maze of the modern world and being the mimesis of its complexity and cultural totality, it has, both for Calvino and Eco, a cosmic vocation.In tracing the lines of a universal literature with a cosmological vocation, both authors think that the ménage à trois of literature with science and philosophy may take a new observation strategy, a completely changed look on things and on the world. In this sense, they are linked to the tradition of the modern novel that, from the beginning, has an inborn encyclopedic vocation, seeing the novel itself as a total work. It is a daring, unrealistic attempt at writing the absolute book, the chimera of a book to end all books, rhizomatic encyclopedia and network of connections at the same time, endless clavis universalis which, according to Mallarmé, allows the connection of Poetry to the Universe. Therefore, in this context, concepts and metaphors of the total novel, labyrinth, library, encyclopedia, as well as the rhetorical and cognitive strategies, such as combinatorial art, enumeration and the list, considered in this paper, become a whole within a literary project aspiring to be a total one, as well as intending to rebuild a lost unity and drawing up a universal history of the world. It is, however, an attempt doomed to failure. Any plans to hold the experience in an exhaustive catalogue of wisdom reveals its delusion: as Eco states, “the semantic global Universe” is an extreme concept, or rather, “a semiotic postulate”, that can never be represented as a whole.